2020
DOI: 10.3389/fimmu.2019.03058
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Inflammatory Pathways in Allergic Asthma and Sickle Cell Disease

Abstract: The underlying pathologies of sickle cell disease and asthma share many characteristics in terms of respiratory inflammation. The principal mechanisms of pulmonary inflammation are largely distinct, but activation of common pathways downstream of the initial inflammatory triggers may lead to exacerbation of both disease states. The altered inflammatory landscape of these respiratory pathologies can differentially impact respiratory pathogen susceptibility in patients with sickle cell disease and asthma. How th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…Further, our study confirmed a higher mean IgE level among SCD HU− pediatric patients, consistent with an adaptive cellular immunity skewed towards a T-helper 2 phenotype; however, this was without statistical significance, ascribable to the small cohort size. An increase in IgE levels occurs much more frequently in children affected by SCD than in the general pediatric population, being associated with a higher risk for both asthma and acute chest syndrome, as a result of an imbalance between type 1 and 2 helper T cells, with adaptive cellular immunity dominated by the latter [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, our study confirmed a higher mean IgE level among SCD HU− pediatric patients, consistent with an adaptive cellular immunity skewed towards a T-helper 2 phenotype; however, this was without statistical significance, ascribable to the small cohort size. An increase in IgE levels occurs much more frequently in children affected by SCD than in the general pediatric population, being associated with a higher risk for both asthma and acute chest syndrome, as a result of an imbalance between type 1 and 2 helper T cells, with adaptive cellular immunity dominated by the latter [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of lung clinical manifestations, such as acute chest syndrome (ACS), asthma and recurrent wheezing, venous thromboembolic disease and sleep-disordered breathing, commonly coexist with SCD [ 60 ]. The association between asthma and SCD has long since been recognized; however, the frequent wheezing that characterizes SCD patients may perhaps account for overdiagnosis of asthma in such a condition [ 61 ]. Of note is that the presence of wheezing, even in the absence of an asthma diagnosis, has been recently proposed as a risk factor for the severity of sickle cell related clinical manifestations [ 62 ].…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…Of note is that the presence of wheezing, even in the absence of an asthma diagnosis, has been recently proposed as a risk factor for the severity of sickle cell related clinical manifestations [ 62 ]. This is of interest since children with SCD and asthma have increased rates of VOCs and ACS and have an increased risk of premature death [ 61 , 63 ]. Epidemiologic studies report a higher prevalence of asthma in the SCD population compared to matched healthy controls.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This inflammation is often accompanied by increased airway responsiveness, which causes recurrent wheezing, shortness of breath, chest tightness, and/or cough ( 1 ). Allergic asthma threatens the lives and health of 300 million people worldwide, with more than 26 million people being affected each year in the United States alone ( 2 ). Despite intense efforts at understanding pathogenic mechanisms and developing strategies to contain this disease in recent decades, the high morbidity and mortality of asthma and subsequent airway remodeling are still difficult to control.…”
mentioning
confidence: 99%